Mechanochemical activation of silicon photothermal material for efficient interfacial solar desalination and wastewater purification - Shridharan, Tatachari Santhanagopalan; Sivanantham, Arumugam; Lee, Jong Ho; Hong, Seo Yeong; Jeong, Yoo Jae; Shin, Seong Sik; Cho, In Sun (Chemical Engineering Journal, 2024)
Solar steam generation (SSG) has emerged as a sustainable solution for addressing water scarcity, and ongoing research has resulted in the development of various photothermal materials that demonstrate exceptional light-absorption capabilities and overall performance. This study presents mechanochemically activated silicon (Si60), which exhibits a high photon-to-heat conversion efficiency for SSG, as an advanced and superior photothermal material. When exposed to simulated sunlight conditions (AM1.5G, 100 mW cm−2), the Si60-coated photothermal membrane demonstrated an impressive evaporation rate of 2.2 kg m−2 h−1 and a high SSG efficiency of 107.9 %. Our investigation revealed that Si60 possessed a minute particle size (∼1.2 µm), nano-scale cracks, and reduced Si-O bond percentage owing to mechanochemical activation (60 h). In addition, it exhibited low thermal conductivity (∼0.33 W m−1 K−1), hydrophilic characteristics, and high photon-to-heat conversion efficiency (∼56.4 %). These characteristics collectively enhanced SSG performance. Moreover, we examined the practical application of the Si60 photothermal membrane in seawater desalination and wastewater purification. Inductively coupled plasma mass spectroscopy (ICP-MS) analysis revealed that the ion concentrations in the collected water were considerably lower than the standards set by the World Health Organization (WHO) in both cases. In addition, we evaluated the SSG performance of a large-area Si60 membrane under natural sunlight conditions. The results demonstrated robust evaporation capabilities of approximately 11 kg m−2 day−1, even under low average solar intensity (0.61 sun). This study underscores the profound impact of mechanochemical activation on bulk silicon, enhancing its photothermal properties and potentially facilitating the development of high-performance desalination systems on a large scale.
Keywords: Condition; Heat conversion efficiencies; Mechano-chemical activation; Performance; Photo-thermal; Solar desalination; Solar steam; Solar steam generation; Steam generation; Wastewater purification; Desalination; Mechanochemical activation; Silicon; Solar steam generation; Wastewater purification